The Effect of Remineralizing Toothpastes on Enamel Surface Roughness after Hybrid Laser Bleaching (An In vitro Study) - Bahar J Selivany; Fadi Al-Hano (College of Dentistry/ University of Baghdad, 2015)
Background: one of the complications of power bleaching is surface roughness of enamel which increases the possibility of post bleaching teeth discoloration. The aim of the present study is to evaluate the effect of toothpaste containing nano hydroxyapatite, NovaMin and kin sense fluoride on surface roughness of human tooth enamel after laser bleaching with 35% hydrogen peroxide bleaching gel. Materials and Methods: Twenty human enamel incisors were cleaned and their labial surface polished up to #1200, then categorized into four equal groups; first group kept without bleaching as a control group, while the remaining three experimental groups were bleached with 35% hydrogen peroxide, and each group treated with a restore paste containing one of the following: nano hydroxyapatite, NovaMin, and Kin fluoride. Bleaching was done with laser hybrid system (DMC Whitening Lase II, Sao Paulo, Brazil). Enamel roughness values assessed by an atomic force microscopy (AA3000, Bosten, USA) before and after treatment with restore tooth paste. Results: Paired t-test used to compare the mean roughness values before and after treatment with each restore paste. One-way analysis of variance and Duncan post hoc tests used to determine the differences between mean roughness values of the groups. A p-value of 0.05 or less considered a significant. The results showed a highly significant statistical differences of remineralization of all types of restore tooth pastes. Conclusions: Nano hydroxyapatite past exhibiting a higher ability to reduce the surface roughness after laser bleaching than other tested pastes.